Designing Data Warehouse for Analysis of Culinary Sales With Multidimensional Modeling – Star Schema Design (Case Study: XYZ Restaurant) - Saputra, Aggry; Zulfachmi, Zulfachmi; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2018)
Fast and accurate information is one of the factors that make a company can be more superior than the other. In order to meet the information needs of various data, it takes a data warehouse where data from data warehouse can be more useful information so that can be used in support of a decision quickly. Star Schema is one dimensional model of data warehouse that has fact tables in the middle and is surrounded by several dimension tables.